Coloniality and imperialism cannot be ignored in analysing the negotiations around the proposed pandemic agreement - David Legge; Tania Cossich (Journal of Critical Public Health)
In his editorial on the negotiations for a pandemic agreement, Petersen (2024) notes that while some provisions have been endorsed by the International Negotiating Body (INB), others remain contested. He questions, with good reason, whether the negotiations will yield more equitable and effective arrangements for pandemic prevention and response.  In this response we argue that the continuing expression of colonial arrogance in global health governance provides important contextual framing regarding vaccine hoarding and of the conflicts over the proposed pandemic agreement and that exploration of this would have added to the usefulness of the editorial.